An efficient method for generation of march tests based on formulas - Harutunyan, Gurgen; Davit Melkumyan; Hasmik Elchyan; Valery Vardanian (Изд-во НАН РА)
A general method for generation of minimal March tests to detect or diagnose any subclass of simple static or dynamic faults in Static RAMs is described. The proposed method is shown to generate all possible March tests satisfying certain necessary conditions for detection of faults. A correspondence between March tests and natural numbers is established that allows construct a formula that enables generation of all March tests detecting certain faults. As an example, the method is applied for construction of new minimal March tests for detection of several subclasses of three-operation dynamic faults. The method can be generalized for detection/diagnosis of any subset of static or dynamic faults.
Keywords: Mathematics